2004
DOI: 10.1080/10409230490460765
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Chemistry and the Origin of the RNA World

Abstract: The demonstration that ribosomal peptide synthesis is a ribozyme-catalyzed reaction makes it almost certain that there was once an RNA World. The central problem for origin-of-life studies, therefore, is to understand how a protein-free RNA World became established on the primitive Earth. We first review the literature on the prebiotic synthesis of the nucleotides, the nonenzymatic synthesis and copying of polynucleotides, and the selection of ribozyme catalysts of a kind that might have facilitated polynucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
248
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 909 publications
(288 citation statements)
references
References 164 publications
5
248
0
1
Order By: Relevance
“…Recent reports describe the possible abiotic production of monomeric RNA precursors from simple feedstocks,1, 2, 3, 4 but advancing to the next level of complexity has been hindered by several constraints 5, 6, 7. Foremost of these is the inherent lack of regiocontrol in the oligomerization of activated ribonucleotides.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports describe the possible abiotic production of monomeric RNA precursors from simple feedstocks,1, 2, 3, 4 but advancing to the next level of complexity has been hindered by several constraints 5, 6, 7. Foremost of these is the inherent lack of regiocontrol in the oligomerization of activated ribonucleotides.…”
mentioning
confidence: 99%
“…Foremost of these is the inherent lack of regiocontrol in the oligomerization of activated ribonucleotides. In the absence of complex macromolecular catalysts, new internucleotide linkages are inevitably forged as both 3′,5′‐ and 2′,5′‐phosphodiester bonds 6, 7, 8. The problem has prompted extensive investigation, ranging from synthetic efforts to favor natural 3′,5′‐bonds,8, 9, 10, 11 to the finding that, below a threshold level, backbone heterogeneity might be compatible with the catalytic and recognition properties of RNA 12.…”
mentioning
confidence: 99%
“…One hundred years later, inspired by Oparin's 1924 suggestion of a material origin of life [2], Miller and Urey [3] showed that subjecting what was then the best hypothesis for the gasses of the prebiotic atmosphere (methane, ammonia, water, and carbon dioxide) to electric discharge was sufficient to produce at least 11 of the 20 then known amino acids making up the proteins of life (actually there are 22 known amino acids of life). Since then, many other similar experiments have demonstrated abiogenic routs to, not only the amino acids, but also to the nucleic acid bases, the ribose-like sugars, and the polyphosphates; the basic constituents of RNA and DNA, the probable first molecules of life [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Models of mutualism and cooperative effects in autocatalytic sets, on quasi-species, the protein world and the RNA world (see for example, [3][4][5][6]) all assume tacitly the homochirality of the implied species. The origin of biological homochirality is thus considered as a separate and disjoint event: the formation of enantiomerically pure polymers is assumed to occur by starting from enantiomerically pure mixtures of their monomers.…”
Section: Introductionmentioning
confidence: 99%